2012
DOI: 10.1186/1744-8069-8-56
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Injury Increases Glutamate-Evoked Calcium Mobilization in Adult Spinal Cord Neurons

Abstract: BackgroundCentral sensitization in the spinal cord requires glutamate receptor activation and intracellular Ca2+ mobilization. We used Fura-2 AM bulk loading of mouse slices together with wide-field Ca2+ imaging to measure glutamate-evoked increases in extracellular Ca2+ to test the hypotheses that: 1. Exogenous application of glutamate causes Ca2+ mobilization in a preponderance of dorsal horn neurons within spinal cord slices taken from adult mice; 2. Glutamate-evoked Ca2+ mobilization is associated with spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…Using live-cell Fura-2 ratiometric analysis in adult spinal cord slices (25), we found that glutamate-evoked [Ca 2+ ] i in lamina II neurons was potentiated at 3 d after CFA and then resolved by day 21 (F 3,17 = 15, P < 0.0001; Fig. 2A); this coincides with the temporal onset and resolution of inflammatory hyperalgesia.…”
mentioning
confidence: 70%
“…Using live-cell Fura-2 ratiometric analysis in adult spinal cord slices (25), we found that glutamate-evoked [Ca 2+ ] i in lamina II neurons was potentiated at 3 d after CFA and then resolved by day 21 (F 3,17 = 15, P < 0.0001; Fig. 2A); this coincides with the temporal onset and resolution of inflammatory hyperalgesia.…”
mentioning
confidence: 70%
“…26,27 The aforementioned neurotransmitters interact with N-methyl-D-aspartate receptor (NMDA), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPA), metabotropic receptors of glutamate (mGluR), neurokinin-1 receptor (NK1R) and purinergic receptors (P2X) of spinal nociceptive projection neurons [28][29][30][31][32][33][34][35] causing their depolarization and the generation of painful signals to be scattered throughout the nociceptive spinothalamic pathway. In turn, this chemical neurotransmission causes an influx of calcium ions in the spinal nociceptive neurons of second order, 36 a process that activates calcium-dependent intracellular cascades, inducing phosphorylation sensitization 37 and ionic channel and membrane receptor overexpression (Table 3). Moreover, the neurotransmitters and Voltage-gated ion channels (increase of their expression)…”
Section: Molecular Neuroplasticity Of Ascending Pain Pathway In Injurmentioning
confidence: 99%
“…pERK is typically observed following high-threshold (Aδ- or C-fiber) or noxious stimulation (Ji et al, 1999), however, during the maintenance phase of chronic pain (> 2 days post CFA) a low-threshold (Aβ-fiber) stimulation (Matsumoto et al, 2008) or light-touch (Gao and Ji, 2010a) can induce spinal pERK expression, suggestive of injury-induced central sensitization (Ji et al, 2003). We found that after pain resolution (21d), light-touch was unable to effectively activate superficial DH neurons unless LS was disinhibited by NTX (Corder et al, 2013); 2) Within spinal cord slices, we visualized intracellular Ca 2+ concentrations ([Ca 2+ ] i ) in populations of DH neurons using Fura-2 labeling and wide-field fluorescence microscopy (Doolen et al, 2012). NTX administration to slices taken from post-hyperalgesia animals precipitated ↑ [Ca 2+ ] I , indicating that LS survives in spinal nociceptive neurons within our slice preparation, and that opioid receptor activity tonically suppresses it (Corder et al, 2013); 3) NTX produced cAMP superactivation in the DH of post-hyperalgesia mice (Corder et al, 2013).…”
Section: Opioid Receptor-masked Sensitizationmentioning
confidence: 99%